Censorship in democracy - Marcel Caesmann; Janis Goldzycher; Matteo Grigoletto; Lorenz Gschwent (University of Zurich, Department of Economics, 2024)
The spread of propaganda, misinformation, and biased narratives from autocratic regimes, especially on social media, is a growing concern in many democracies. Can censorship be an effective tool to curb the spread of such slanted narratives? In this paper, we study the European Union's ban on Russian state-led news outlets after the 2022 Russian invasion of Ukraine. We analyze 775,616 tweets from 133,276 users on Twitter/X, employing a difference-in-differences strategy. We show that the ban reduced pro-Russian slant among users who had previously directly interacted with banned outlets. The impact is most pronounced among users with the highest pre-ban slant levels. However, this effect was short-lived, with slant returning to its pre-ban levels within two weeks post-enforcement. Additionally, we find a detectable albeit less pronounced indirect effect on users who had not directly interacted with the outlets before the ban. We provide evidence that other suppliers of propaganda may have actively sought to mitigate the ban's influence by intensifying their activity, effectively counteracting the persistence and reach of the ban.
Keywords: D72; D78; L82; P16; 330; Censorship; Policy effectiveness; Text-as-data; Media slant